Certain inequalities of Kober and Lazarevic type - Bagul, Yogesh J.; Panchal, Satish K. (The Journal of the Indian Mathematical Society, 2022)
In this work, the authors present new lower and upper bounds for cos x and cosh x, thus improving some generalized inequalities of Kober and Lazarevic type.